Innovation support measures in Ukraine: some legislative and organizational aspects - Yehorov, I.Yu. (Наука, технології, інновації, 2017)
This article contains brief description of the situation in innovation sphere in Ukraine, based on utilization of traditional statistics of innovation activities, results of calculations of the place of Ukraine in the EU Innovation Scoreboard. Special attention is paid to the evolution of the legal foundations of support in innovation activities and the existing elements of innovation infrastructure. Also, it focuses the importance in the innovations ventures like technoparks, science parks and others have for the future of Ukraine. Finally, conclusions and recommendations are made about the current status of the S&T and innovation activities in the country. У цій статті подано короткий опис ситуації в інноваційній сфері в Україні на основі використання традиційної статистики інноваційної діяльності та результатів розрахунків місця України в Інноваційному табло ЄС. Особлива увага приділяється розвитку правових основ підтримки інноваційної діяльності та існуючих елементів інноваційної інфраструктури. Також у статті підкреслюється важливість для майбутнього України впровадження так форм підтримки інновацій, як технопарки, наукові парки тощо. Наведено висновки та рекомендації щодо поточного стану науково-технічної та інноваційної діяльності в країні. В этой статье подано краткое описание ситуации в инновационной сфере в Украине на основе использования традиционной статистики инновационной деятельности и результатов расчетов места Украины в Инновационном табло ЕС. Особое внимание уделяется развитию правовых основ поддержки инновационной деятельности и существующих элементов инновационной инфраструктуры. Также в статье подчеркивается важность для будущего Украины внедрения таких форм поддержки инноваций, как техно-парки, научные парки и др. Приведены выводы и рекомендации относительно текущего состояния научно-технической и инновационной деятельности в стране.